Preparation method and application of high-strength Au / Pt alloy

Through electrochemical corrosion and electrochemical deposition technology combined with high-temperature annealing, high-strength Au/Pt alloys were prepared, which solved the limitations of the existing amplitude modulation decomposition technology in the applicability, component modulation and thermodynamic dynamic conditions of the alloy system, and significantly improved the performance of the alloy.

CN119859828AInactive Publication Date: 2025-04-22JIANGSU UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510234146.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-28
Publication Date
2025-04-22
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing amplitude modulation decomposition technology has many limitations in the applicability of the alloy system, the control of component modulation amplitude and interface morphology structure, and the limitation of thermodynamic and kinetic conditions, resulting in the limitation of the strength, wear resistance and high-temperature fatigue resistance of Au/Pt alloys.

Method used

Using a combination of electrochemical corrosion and electrochemical deposition, Pt is selectively dissolved through a three-electrode system and formed nanoporous Pt. Then Pt is backfilled into the nanopores by electrochemical deposition technology, and high-strength Au/Pt alloys are prepared by high-temperature annealing.

Benefits of technology

It effectively breaks through the limitations of traditional amplitude modulation decomposition technology, realizes precise control of the modulation amplitude and interface structure of Au/Pt alloy components, and significantly improves the strength, wear resistance and high-temperature fatigue resistance of the alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859828A_ABST
    Figure CN119859828A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of materials, and discloses a preparation method and application of a high-strength Au / Pt alloy. Nanoporous Pt in the material is backfilled into nanopores formed by electrochemical corrosion of solid solution Au-Pt through an electro-deposition method, and Au / Pt alloy with a gradient nanostructure is formed by controlling the electrochemical deposition speed. The method comprises the steps that Pt in a solid solution Au-Pt is selectively dissolved through electrochemical corrosion, undissolved Pt atoms are promoted to be self-assembled to form nano-porous Pt, then Pt is backfilled into nano-pores through electrochemical deposition, and then the high-strength Au / Pt alloy is prepared through high-temperature annealing. On one hand, the method breaks through the defects that a traditional preparation method is complex and the structure is not easy to regulate; on the other hand, the material retains coarse grains of the precursor alloy, the inside of the grains is composed of Au and Pt phases which are of a face-centered cubic structure, are consistent in crystal orientation and are communicated with each other in the nanometer size, the gradient nanometer structure is achieved, and the obdurability, the abrasion resistance, the damping capacity, the high-temperature performance and the like of the material are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of material science, and specifically relates to a preparation method and application of a high-strength Au / Pt alloy. Background Art

[0002] In the field of materials science, especially in alloy preparation and microstructure control, researchers have been committed to exploring new preparation methods and material structures to improve the performance and function of materials. Among them, modulated decomposition is an important material microstructure control technology, through which periodic changes in material composition and structure can be achieved, thereby changing the physical and chemical properties of the material. The existing modulated decomposition technology has many limitations in application, which are mainly reflected in the following aspects: first, the applicable alloy system is relatively limited, and most alloy systems cannot achieve modulated decomposition by this method; second, the composition modulation amplitude and interface morphology structure are difficult to control and optimize, which limits the further improvement of material performance; finally, the limitations of thermodynamic and kinetic conditions greatly limit the scope of application of this method. Therefore, the problems or shortcomings of the existing technology in this field mainly include: limited applicable alloy system, difficult to control composition modulation amplitude and interface morphology structure, and limitations of thermodynamic and kinetic conditions.

[0003] Au / Pt alloy, or gold-platinum alloy, is an alloy material composed of gold (Au) and platinum (Pt). The hardness of Au / Pt alloy is relatively large, and it has good toughness, which enables it to maintain good shape stability and deformation resistance during processing. And because gold and platinum are both chemically stable metals, Au / Pt alloy has excellent corrosion resistance and can resist the erosion of a variety of chemical substances. It has important application value in the fields of high-end chemical manufacturing and biomaterials. Traditional Au / Pt alloys are made by melting casting and powder metallurgy methods. Due to the limitations of thermodynamic and kinetic conditions, their applicable alloy systems are relatively limited, and it is difficult to control and optimize the composition modulation amplitude and interface morphology structure. Therefore, the Au / Pt alloy prepared by the current process has great limitations, and there are still great limitations in terms of toughness, wear resistance, and high-temperature fatigue resistance. Summary of the invention

[0004] In order to improve the toughness, wear resistance, and high temperature fatigue resistance of Au / Pt alloy, the object of the present invention is to provide a method for preparing a high-strength Au / Pt alloy, comprising the following steps:

[0005] (1) Electrochemical corrosion: A three-electrode system is used to selectively dissolve Pt in the precursor Au-Pt alloy, causing the undissolved Pt atoms to self-assemble into nanoporous Pt to obtain a solid solution;

[0006] (2) using the solid solution obtained in step (1) as a working electrode, a counter electrode as pure Ag wire, and a reference electrode as an Ag / AgCl electrode to form a three-electrode system, and using electrochemical deposition technology to backfill Pt into the nanopores;

[0007] (3) The product obtained in step (2) is subjected to high temperature annealing to prepare a high-strength Au / Pt alloy.

[0008] In step (1), in the three-electrode system, the working electrode is a precursor Au-Pt alloy; the counter electrode is a pure Ag wire; the reference electrode is an Ag / AgCl electrode; the electrochemical corrosion electrolyte is 70wt% or more HClO4 or 70wt% or more H2SO4 or a composite solution thereof;

[0009] In step (1), the electrochemical corrosion potential is 0.3-1V; the corrosion time is 5min-120min;

[0010] In step (2), the electrochemical deposition electrolyte is 10 wt % or more of PtClO4;

[0011] In step (2), the electrochemical deposition potential is 0.3-1V; the corrosion time is 5min-120min;

[0012] In step (3), the temperature of high temperature annealing is 800-1200° C.; the time of high temperature annealing is 1-3 hours;

[0013] In step (3), the high temperature annealing atmosphere is Ar or N2 inert gas;

[0014] In step (3), the high temperature annealing and rapid cooling time is 1-10 min.

[0015] In the Au / Pt alloy prepared by the present invention, the mass ratio of Au to Pt is 9-6:1-4.

[0016] The new material prepared by the present invention retains the coarse grains of the precursor alloy, and the crystals are composed of nanometer two phases with the same face-centered cubic structure, consistent crystal orientation, and mutual penetration. The two phases are separated by a three-dimensional, continuous, smooth and curved phase interface, and have a gradient nanostructure.

[0017] The high-strength Au / Pt alloy prepared by the present invention is applied to the fields of ships, marine engineering, deep-sea space stations, submarine oil and gas pipelines, wind turbine blades or humanoid robot joints.

[0018] The beneficial effects of the present invention are:

[0019] (1) Solving the problem of limited applicable alloy systems of traditional spinodal decomposition technology. The present invention breaks through the inherent limitations of traditional spinodal decomposition through electrochemical corrosion and electrochemical deposition methods, and prepares Au / Pt alloys with excellent performance.

[0020] (2) It solves the problem that the traditional amplitude modulation decomposition technology is difficult to control and optimize the amplitude of the component modulation and the interface morphology structure. The present invention can effectively control and optimize the amplitude of the component modulation and the interface morphology structure by precisely controlling the process of electrochemical deposition and dealloying corrosion. The material retains the coarse grains of the precursor alloy, and the crystals are composed of Au and Pt phases that are both face-centered cubic, have consistent crystal orientation, and are interconnected at the nanometer scale; thereby improving the material performance.

[0021] (3) The problem that the traditional spinodal decomposition technology is restricted by thermodynamic and kinetic conditions is solved. The present invention can effectively control the thermodynamic and kinetic conditions through the methods of electrochemical corrosion and electrochemical deposition, thereby expanding the application scope of spinodal decomposition technology.

[0022] (4) The toughness, wear resistance, shock absorption and high temperature fatigue resistance of Au / Pt alloy prepared by the existing process are improved. The present invention innovatively uses a method combining electrochemical corrosion and electrochemical deposition to prepare Au / Pt alloy with excellent performance. It has important application value in the fields of high-end chemical manufacturing, biomaterials, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a TEM image of the high-strength Au / Pt alloy prepared in the present invention. DETAILED DESCRIPTION

[0024] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited thereto.

[0025] Embodiment 1:

[0026] The purpose of this embodiment is to prepare a high-strength Au / Pt alloy, comprising the following steps:

[0027] (1) A three-electrode system is adopted, wherein the working electrode is a precursor alloy; the counter electrode is a pure Ag wire; the reference electrode is an Ag / AgCl electrode; the electrochemical corrosion electrolyte is 70wt% HClO4; the electrochemical corrosion potential is 0.5V; and the corrosion time is 60min;

[0028] The solid solution is prepared by selectively dissolving Pt in the Au-Pt solid solution through electrochemical corrosion technology, and promoting the self-assembly of undissolved Pt atoms to form nanoporous Pt.

[0029] (2) A three-electrode system is used, wherein the working electrode is the solid solution prepared in step (1); the counter electrode is pure Ag wire; the reference electrode is an Ag / AgCl electrode; the electrochemical deposition electrolyte is 10 wt% or more PtClO4; the electrochemical deposition potential is 0.5 V; the corrosion time is 60 min; and Pt is backfilled into the nanopores by electrochemical deposition technology.

[0030] (3) In an Ar atmosphere, high-temperature annealing was performed at 1000°C for 2 h, and the high-temperature annealing rapid cooling time was 5 min to prepare a high-strength Au / Pt alloy. The mass ratio of Au to Pt in the prepared alloy was 9:1.

[0031] The hardness of the prepared Au / Pt alloy is 8.32 GPa and the modulus is 163.5 GPa.

[0032] Embodiment 2:

[0033] The purpose of this embodiment is to prepare a high-strength Au / Pt alloy, comprising the following steps:

[0034] (1) A three-electrode system is adopted, wherein the working electrode is a precursor alloy; the counter electrode is a pure Ag wire; the reference electrode is an Ag / AgCl electrode; the electrochemical corrosion electrolyte is 98wt% or more H2SO4; the electrochemical corrosion potential is 0.5V; and the corrosion time is 60min;

[0035] The solid solution is prepared by selectively dissolving Pt in the Au-Pt solid solution through electrochemical corrosion technology, and promoting the self-assembly of undissolved Pt atoms to form nanoporous Pt.

[0036] (2) A three-electrode system is used, wherein the working electrode is the solid solution prepared in step (1); the counter electrode is pure Ag wire; the reference electrode is an Ag / AgCl electrode; the electrochemical deposition electrolyte is 10 wt% or more PtClO4; the electrochemical deposition potential is 0.5 V; the corrosion time is 60 min; and Pt is backfilled into the nanopores by electrochemical deposition.

[0037] (3) In an Ar atmosphere, high-temperature annealing was performed at 1000°C for 2 h, and the high-temperature annealing rapid cooling time was 5 min to prepare a high-strength Au / Pt alloy. The mass ratio of Au to Pt in the prepared alloy was 8:2.

[0038] The hardness of the prepared Au / Pt alloy is 9.01 GPa and the modulus is 171.5 GPa.

[0039] Embodiment 3:

[0040] The purpose of this embodiment is to prepare a high-strength Au / Pt alloy, comprising the following steps:

[0041] (1) A three-electrode system is adopted, wherein the working electrode is a precursor alloy; the counter electrode is a pure Ag wire; the reference electrode is an Ag / AgCl electrode; the electrochemical corrosion electrolyte is 70wt% HClO4; the electrochemical corrosion potential is 1V; and the corrosion time is 60min;

[0042] The solid solution is prepared by selectively dissolving Pt in the Au-Pt solid solution through electrochemical corrosion technology, and promoting the self-assembly of undissolved Pt atoms to form nanoporous Pt;

[0043] (2) A three-electrode system is used, wherein the working electrode is the solid solution prepared in step (1); the counter electrode is pure Ag wire; the reference electrode is an Ag / AgCl electrode; the electrochemical deposition electrolyte is 10 wt% or more PtClO4; the electrochemical deposition potential is 1 V; the corrosion time is 60 min; and Pt is backfilled into the nanopores by electrochemical deposition;

[0044] (3) In an Ar atmosphere, high-temperature annealing was performed at 1000°C for 2 h, and the high-temperature annealing rapid cooling time was 5 min to prepare a high-strength Au / Pt alloy. The mass ratio of Au to Pt in the prepared alloy was 7:3.

[0045] The hardness and modulus of the prepared Au / Pt alloy are 7.32 GPa and 168.5 GPa respectively.

[0046] Embodiment 4:

[0047] The purpose of this embodiment is to prepare a high-strength Au / Pt alloy, comprising the following steps:

[0048] (1) A three-electrode system is adopted, wherein the working electrode is a precursor alloy; the counter electrode is a pure Ag wire; the reference electrode is an Ag / AgCl electrode; the electrochemical corrosion electrolyte is 70wt% HClO4; the electrochemical corrosion potential is 0.5V; and the corrosion time is 120min;

[0049] The solid solution is prepared by selectively dissolving Pt in the Au-Pt solid solution through electrochemical corrosion technology, and promoting the self-assembly of undissolved Pt atoms to form nanoporous Pt;

[0050] (2) A three-electrode system is used, wherein the working electrode is the solid solution prepared in step (1); the counter electrode is pure Ag wire; the reference electrode is an Ag / AgCl electrode; the electrochemical deposition electrolyte is 10 wt% or more PtClO4; the electrochemical deposition potential is 0.5 V; the corrosion time is 120 min; and Pt is backfilled into the nanopores by electrochemical deposition;

[0051] (3) In an Ar atmosphere, high-temperature annealing was performed at 1000°C for 2 h, and the high-temperature annealing rapid cooling time was 5 min to prepare a high-strength Au / Pt alloy. The mass ratio of Au to Pt in the prepared alloy was 6:4.

[0052] The hardness of the prepared Au / Pt alloy is 6.89 GPa and the modulus is 175.2 GPa.

[0053] like Figure 1 As shown in the figure, the new material retains the coarse grains of the precursor alloy, and its crystals are composed of nano-duplex phases with the same face-centered cubic structure, consistent crystal orientation, and mutual penetration. The two phases are separated by a three-dimensional continuous, smooth and curved phase interface, and have a gradient nanostructure.

Claims

1. A method for preparing a high-strength Au / Pt alloy, characterized in that: The following steps are involved: (1) Electrochemical corrosion: A three-electrode system is used to selectively dissolve Pt in the precursor Au-Pt alloy, causing the undissolved Pt atoms to self-assemble into nanoporous Pt to obtain a solid solution; (2) using the solid solution obtained in step (1) as a working electrode, a counter electrode as pure Ag wire, and a reference electrode as an Ag / AgCl electrode to form a three-electrode system, and using electrochemical deposition technology to backfill Pt into the nanopores; (3) The product obtained in step (2) is subjected to high temperature annealing to prepare a high-strength Au / Pt alloy.

2. The method for preparing a high-strength Au / Pt alloy according to claim 1, characterized in that: In step (1), in the three-electrode system, the working electrode is the precursor Au-Pt alloy; the counter electrode is a pure Ag wire; and the reference electrode is an Ag / AgCl electrode.

3. The method for preparing a high-strength Au / Pt alloy according to claim 1, characterized in that: In step (1), in the three-electrode system, the electrochemical corrosion electrolyte is more than 70wt% HClO4 or more than 70wt% H2SO4 or a composite solution thereof.

4. The method for preparing a high-strength Au / Pt alloy according to claim 1, characterized in that: In step (1), the electrochemical corrosion potential is 0.3-1V; the corrosion time is 5min-120min.

5. The method for preparing a high-strength Au / Pt alloy according to claim 1, characterized in that: In step (2), the electrochemical deposition electrolyte contains more than 10 wt % PtClO4.

6. The method for preparing a high-strength Au / Pt alloy according to claim 1, characterized in that: In step (2), the potential of electrochemical deposition is 0.3-1V; and the corrosion time is 5min-120min.

7. The method for preparing a high-strength Au / Pt alloy according to claim 1, characterized in that: In step (3), the temperature of high temperature annealing is 800-1200° C.; the time of high temperature annealing is 1-3 hours.

8. The method for preparing a high-strength Au / Pt alloy according to claim 1, characterized in that: In step (3), the high temperature annealing atmosphere is Ar or N2 inert gas.

9. The method for preparing a high-strength Au / Pt alloy according to claim 1, characterized in that: In step (3), the high temperature annealing and rapid cooling time is 1-10 min.

10. The high-strength Au / Pt alloy prepared by the preparation method according to any one of claims 1 to 9 is applied to the fields of ships, marine engineering, deep-sea space stations, submarine oil and gas pipelines, wind turbine blades or humanoid robot joints.